THE ROLE OF TRANSPORT AND LOGISTICS CENTERS IN UZBEKISTAN - Nurmatov Khondamir Yodgorbek ugli; Rustamova Dilsabo Dzhuraevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article substantiates the development of modern logistics in Uzbekistan and the possibilities of its introduction, as well as the need to establish transport and logistics centers.